Bloodstream Infections Caused by Enterococcus spp：A 10-year Retrospective Analysis at a Tertiary Hospital in China - 郑金鑫 李晖 蒲彰雅 王红燕 邓向斌 刘晓军 邓启文 余治健 (Journal of Huazhong University of Science and Technology. Medical sciences, 2017)
In order to discover the risk factors for 30-day mortality in bloodstream infections（BSI） caused by Enterococcus spp.strains,we explored the clinical and therapeutic profile of patients with Enterococcus spp.BSI and the characteristics of this condition.A total of 64 patients with BSI caused by Enterococcus spp.who were treated in our hospital between 2006 and 2015 were included in the study.The clinical features of patients,microbiology,and 30-day mortality were collected from the electronic medical records database and analyzed.The results showed that there were 38 patients infected by Enterococcus faecalis（E.faecalis）,24 by Enterococcus faecium（E.faecium）,1 by Enterococcus casseliflavus（E.casseliflavus）,and 1 by Enterococcus gallinarum（E.gallinarum）.A Charlson comorbidity score ≥5,corticosteroid treatment,placement of catheters or other prosthetic devices and history of antibiotic use were found more frequently in E.faecium BSI patients than in E.faecalis patients（P=0.017,P=0.027,P=0.008 and P=0.027,respectively）.Furthermore,the univariate and multivariate analysis showed that corticosteroid treatment（OR=17.385,P=0.008）,hospital acquisition（OR=16.328,P=0.038）,and vascular catheter infection（OR=14.788,P=0.025） were all independently associated with 30-day mortality.Our results indicate that E.faecalis and E.faecium are two different pathogens with unique microbiologic characteristics,which cause different clinical features in BSI,and the empiric antimicrobial treatments are paramount for patients with enterococcal BSI.